Oral Macrocystis pyrifera Fucoidan Administration Exhibits Anti-Inflammatory and Antioxidant Properties and Improves DSS-Induced Colitis in C57BL/6J Mice - Tauseef Ahmad; Muhammad Ishaq; Samuel Karpiniec; Ahyoung Park; Damien Stringer; Neeraj Singh; Vishal Ratanpaul; Karen Wolfswinkel; Helen Fitton; Vanni Caruso; Rajaraman Eri (MDPI AG, 2022)
Inflammatory bowel disease (IBD) is a complex and multifactorial disorder characterised by relapsing and remitting inflammation of the intestinal tract. Oxidative stress (OS) is the result of an imbalance between production and accumulation of reactive oxygen species (ROS), which has been associated with inflammatory responses and implicated in the exacerbation of IBD. Fucoidan, a sulfated polysaccharide from brown seaweed, is a well-known anti-inflammatory agent and emerging evidence indicates that fucoidan extracts from Macrocystis pyrifera (MPF and DP-MPF) may also modulate oxidative stress. This study investigated the impact of fucoidan extracts, MPF and DP-MPF in a dextran sodium sulphate (DSS)-induced mouse model of acute colitis. 3% DSS was administered in C57BL/6J male mice over a period of 7 days, and MPF and DP-MPF were co-administered orally at a dose of 400 mg/kg body weight. Our results indicated that MPF and DP-MPF significantly prevented body weight loss, improved the disease activity index (DAI), restored colon lengths, reduced the wet colon weight, reduced spleen enlargement, and improved the overall histopathological score. Consistent with the reported anti-inflammatory functions, fucoidan extracts, MPF and DP-MPF significantly reduced the colonic levels of myeloperoxidase (MPO), nitric oxide (NO), malondialdehyde (MDA) and increased the levels of antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT). In addition, MPF and DP-MPF significantly inhibited levels of pro-inflammatory cytokines in colon-derived tissues. Collectively, our results indicate that MPF and DP-MPF exhibited anti-inflammatory and antioxidant effects representing a promising therapeutic strategy for the cure of IBD.